2011
DOI: 10.1007/s11262-011-0695-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of novel picornaviruses in chickens and turkeys

Abstract: Fecal specimens, including swabs and litter extracts, collected from chickens, domestic ducks, turkeys, and Canadian geese were tested using degenerate primers targeting regions encoding for conserved amino acid motifs (YGDD and DY(T/S)(R/K/G)WDST) in calicivirus RNA-dependent RNA polymerases. Similar motifs are also present in other RNA viruses. Two fecal specimens and 18 litter extracts collected from chickens and turkeys yielded RT-PCR products. BLAST search and phylogenetic analysis revealed that all ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 20 publications
4
23
0
Order By: Relevance
“…Previous metagenomic studies into the avian gut microbiome have identified multiple picornavirus species in disease-affected and healthy birds, findings which have been echoed in the present study. However, the pathogenic potential of these viruses in avian species remains relatively unknown due to the large amount of genetic variation observed among these viruses Farkas et al, 2012;Bullman et al, 2014;Zhou et al, 2015). In the present study picornaviruses were commonly found alongside the Astroviridae, Caliciviridae, Parvoviridae, and bacteriophage families (Table 1) and seem to be prevalent in growth-stunted birds.…”
Section: Rna Virome Analysismentioning
confidence: 53%
“…Previous metagenomic studies into the avian gut microbiome have identified multiple picornavirus species in disease-affected and healthy birds, findings which have been echoed in the present study. However, the pathogenic potential of these viruses in avian species remains relatively unknown due to the large amount of genetic variation observed among these viruses Farkas et al, 2012;Bullman et al, 2014;Zhou et al, 2015). In the present study picornaviruses were commonly found alongside the Astroviridae, Caliciviridae, Parvoviridae, and bacteriophage families (Table 1) and seem to be prevalent in growth-stunted birds.…”
Section: Rna Virome Analysismentioning
confidence: 53%
“…Furthermore, the presence of a putative second ORF in partial nucleotide sequences of chicken and turkey picornaviruses has been identified in silico (5).…”
Section: Importancementioning
confidence: 99%
“…The largest (still incomplete) picornavirus genome is THV, a virus associated with liver necrosis and enteritis in turkeys, which belongs to the species Melegrivirus A (genus Megrivirus) and consists of Ͼ9,040 nucleotides (nt), although neither the full length of the 5= UTR nor the complete 3= UTR were determined (7). Additionally, two partial 3D/3= UTR sequence fragments (1,327 nt), closely related to THV, have been identified in turkeys and chickens (5). Recently, two novel picornaviruses (mesivirus 1 and 2) most closely related to megriviruses were identified from wild pigeons.…”
Section: Importancementioning
confidence: 99%
“…However, picornavirus taxonomy is still in flux, as next-generation sequencing technologies facilitate metagenomics studies using viral nucleic acid-containing specimens. Analysis of viral genomes without prior virus isolation led to the identification of more than 30 approved or tentative picornavirus species from humans (cosavirus [3], salivirus [4], saffold virus [5], and rhinovirus-C [6]), rodents (mosavirus, rosavirus, and murine kobuvirus [7]), pinnipeds (seal picornavirus [8] and California sea lion sapelovirus [9]), domestic cats and dogs (feline picornavirus [10], canine picornavirus [11], canine kobuvirus [12], and canine picodicistrovirus [2]), ungulates (bovine hungarovirus, ovine hungarovirus [13], swine pasivirus [14], and porcine kobuvirus [15]), birds (turdiviruses 1 to 3 [16], turkey hepatitis virus [17], pigeon picornaviruses A and B [18], quail picornavirus [19], and gallivirus [20]), and bats (bat picornaviruses 1 to 3 [21], bat kobuvirus-like virus [22], Rhinolophus affinis picornavirus, Ia io picornavirus, and Miniopterus schreibersii picornavirus [23]). …”
mentioning
confidence: 99%